PRÁTICAS SOCIAIS E PLANEJAMENTO TURÍSTICO NO MUNICÍPIO DE IRATI-PR, SOB O ENFOQUE DAS CATEGORIAS ANALÍTICAS GEOGRÁFICAS: LUGAR E PAISAGEM - Tchmolo, Maycon Luiz (2012)
This dissertation aimed to: investigate the congruences and inconsistencies between tourism planning for the city of Irati-PR and social practices of appropriation and exploitation of landscapes experienced, while the collective heritage of the local population. And specific objectives are: a) To discuss the setting of the city of socio spacial Irati from the early twentieth century; b) Analyze the project planning to tour the sights of Irati headquarters and surrounding districts; c) Elaborate on the notions of representation and perception of lived space, landscape and place; d) Verify empirically the degree of enhancement of the landscapes of the population lived in the daily of Irati in terms of matrices of evaluative places; e) Comparing the points. d.ttractions highlighted in the project planning tour with the landscapes experienced by residents of Irati. The methodological procedures there was a questionnaire for the local population; interview with those responsible for tourism planning in Irati, and photographic record of the landscapes mentioned in the questionnaires by local resident. The results were clearly spoken like those landscapes as those experienced by the tourist and resident of Irati as well as the identification of the lack of tourism in the municipality in question. However, those areas considered tourist, there is the realization of social practices of the most different orders, depending on much of the landscape that it presents. It was noticed too, the connection between subject and subjective place, where the local representation endows landscapes through their knowledge and experiences.